1997
DOI: 10.1002/(sici)1097-0185(199710)249:2<249::aid-ar12>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Development of Meckel's cartilage in the symphyseal region in man

Abstract: Background: The aim of this work is to clarify the aspects which are at present most controversial about the development of the anterior segments of Meckel's cartilage, such as the role of and determination of the area that is incorporated in the development of the human mandible.Methods: Light microscope studies were done on 25 embryos and human fetuses from the collection of the Institute of Embryology at the University Complutense of Madrid and the Department of Morphological Science from the University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
1
28
1
1
Order By: Relevance
“…Initial ossification of facial bones began but, at the skull base, the primary cartilages formed a continuous mass of skeleton (Diewert, 1985). The bending of cartilage is also observed in Meckel's cartilage (Rodrıguez-Vazquez et al, 1997;Rodrıguez-Vazquez et al, 2013) possibly to adjust the cartilage to growth of facial structures. Diewert (1985) stated that Hematoxylin-eosin staining.…”
Section: Discussionmentioning
confidence: 99%
“…Initial ossification of facial bones began but, at the skull base, the primary cartilages formed a continuous mass of skeleton (Diewert, 1985). The bending of cartilage is also observed in Meckel's cartilage (Rodrıguez-Vazquez et al, 1997;Rodrıguez-Vazquez et al, 2013) possibly to adjust the cartilage to growth of facial structures. Diewert (1985) stated that Hematoxylin-eosin staining.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the intramembranous ossification as well as the condensed cellular mesenchyme of the condylar blastema was closely associated with a portion of perichondral fibrous tissue of the Meckel cartilage. Because the primary intramembranous ossification of the mandible greatly affects the following histomorphogenetic processes of the whole mandible (Bareggi et al, 1995;Berraquero et al, 1995;Orliaguet et al, 1993bOrliaguet et al, , 1994Rodriguez-Vazquez et al, 1997b;Tomo et al, 1997), we accentuate the primary intramembranous ossification and named it as the mandibular primary growth center (MdPGC). The MdPGC was approximated to the middle portion but lateral in position of the Meckel cartilage in the early embryonal period.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it was frequently insisted that there is no direct connection between the Meckel's cartilage and embryonal mandible, many authors still believe that the Meckel's cartilage, as a core cartilage of first branchial arch, plays some role to induce mandibular growth (Plessis et al, 1991;Yamasaki et al, 1991;Shum et al, 1993;Kjaer, 1997;Rodriguez-Vazquez et al, 1997a, 1997bTrichilis and Wroblewski, 1997;Ishizeki et al, 1999). It was also reported that the Meckel's cartilage is closely associated with the periosteum of the embryonal mandible, and that the genioglossus muscle is primarily attached to the Meckel's cartilage and successively relocated its fusion into the ossifying mandible (Lee et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the Meckel's cartilage is closely associated with the periosteum of the embryonal mandible, and that the genioglossus muscle is primarily attached to the Meckel's cartilage and successively relocated its fusion into the ossifying mandible (Lee et al, 1990). But the direct histogenetic effect of Meckel's cartilage for the mandibular development was frequently debated by many authors (Plessis et al, 1991;Orliaguet et al, 1994;Rodriguez-Vazquez et al, 1997b;Lee et al, 2001;Radlanski et al, 2003;Lorentowicz-Zagalak et al, 2005). In this study, we found that the MdPGC is produced by the intramembranous ossification, and that it becomes the primary backbone of fetal mandible not affected by secondary appositional growth of bone by the tension of functional muscular forces.…”
Section: Discussionmentioning
confidence: 99%